Circadian Disruption: comparing humans with mice. (October 2013) - Radetsky, Leora C.; Rea, Mark S.; Bierman, Andrew; Figueiro, Mariana G.
Abstract : Disruption of the 24-h light-dark cycle has been implicated as an endocrine disruptor and linked to increased morbidity and mortality in animal studies. Previously reported measurements of circadian disruption in day-shift and rotating-shift nurses were compared with new mouse data where the light-dark patterns simulated shiftwork. Phasor magnitudes, a measure of circadian entrainment, were shown to be similar for humans and for mice when exposed to similar patterns of light and dark. Phasor analyses may be a useful method for quantitatively bridging ecological measurements of circadian disruption in human with parametric studies of health outcomes in a mouse model.